Nuevos registros de Puya (Bromeliaceae) en el departamento de Lambayeque, Perú - Ayasta, José E. (2021)
This study provides an annotated checklist of the Puya (Bromeliaceae) species registered from Lambayeque Department; Peru. A total of five species are reported, four are registered for the first time and one of them is confirmed as endemism of Lambayeque Andes. Species were from the seasonal Dry Forest (BSe), Desert Scrub-Dry Forest transition (MD-BS) and Jalca (JA) ecoregions. A key for the Puya reported species is presented and the reasons for endemisms, threats and their categorization criteria are discussed.